2016
DOI: 10.1007/s11694-016-9345-9
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and reconstitution of whole wheat flour and its effect on dough and chapatti quality

Abstract: Fractionation and reconstitution techniques were utilized to study the contribution of flour fractions mainly gluten in chapatti dough rheology and baking performance of chapatti. Micro-scale rheological methods and micro scale baking test on the basis of 10 g flour were used. Two Indian wheat cultivars (NIAW-301 and NIAW-34) were studied. Fractionation which involved defatting of flour, isolation of gluten, collection of aqueous suspension and separation into a soluble fraction and two starch fractions (upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A similar relationship between a protein with dough machinability has been reported (Suhendro et al 1993).The gluten content of flour directly proportional to dough hardness (r = 0.87, P \ 0.01) and cohesiveness of dough (r = 0.85, P \ 0.01) but inversely proportional to the spreadability of dough (-0.93, P \ 0.01). Arya et al (2016) also reported the similar relationship gluten content of flour with hardness and cohesiveness of the dough. Damaged starch correlated positively to farinoghraphic water absorption (r = 0.75, P \ 0.01), Dough stickiness (r = 0.98, P \ 0.01) and negatively correlated to dough development time Cohesiveness (ratio) 0.80 ± 0.00 c 0.77 ± 0.00 c 0.72 ± 0.00 b 0.66 ± 0.02 a Appearance 7.0 ± 0.00 a 6.0 ± 0.00 a 7.0 ± 0.00 a 6.0 ± 0.00 a Colour 7.0 ± 0.00 a 6.0 ± 0.00 a 8.0 ± 0.00 a 7.0 ± 0.00 a Texture 8.67 ± 0.57 c 7.0 ± 0.00 b 6.0 ± 0.00 a 6.0 ± 0.00 a Mouthfeel 8.67 ± 8.66 c 7.0 ± 0.00 b 6.0 ± 0.00 a 6.0 ± 0.00 a Taste 8.0 ± 0.00 a 7.0 ± 0.00 a 8.0 ± 0.00 a 7.0 ± 0.00 a Overall acceptability 8.33 ± 0.28 d 7.0 ± 0.00 b 7.50 ± 0.00 c 6.0 ± 0.00 a a All the values are mean ± SD of three individual determinations b Means followed by the same superscript along the row are not significantly different using duncan multiple ranges test at 5% probability level (r = -0.93, P \ 0.01), dough stability (r = -0.94, P \ 0.01) and work of adhesion (r = -0.70, P \ 0.01).…”
Section: Physicochemical Properties Of Wheat Flours and Correlation To The Dough Rheological Properties Of Wheat Flourmentioning
confidence: 57%
“…A similar relationship between a protein with dough machinability has been reported (Suhendro et al 1993).The gluten content of flour directly proportional to dough hardness (r = 0.87, P \ 0.01) and cohesiveness of dough (r = 0.85, P \ 0.01) but inversely proportional to the spreadability of dough (-0.93, P \ 0.01). Arya et al (2016) also reported the similar relationship gluten content of flour with hardness and cohesiveness of the dough. Damaged starch correlated positively to farinoghraphic water absorption (r = 0.75, P \ 0.01), Dough stickiness (r = 0.98, P \ 0.01) and negatively correlated to dough development time Cohesiveness (ratio) 0.80 ± 0.00 c 0.77 ± 0.00 c 0.72 ± 0.00 b 0.66 ± 0.02 a Appearance 7.0 ± 0.00 a 6.0 ± 0.00 a 7.0 ± 0.00 a 6.0 ± 0.00 a Colour 7.0 ± 0.00 a 6.0 ± 0.00 a 8.0 ± 0.00 a 7.0 ± 0.00 a Texture 8.67 ± 0.57 c 7.0 ± 0.00 b 6.0 ± 0.00 a 6.0 ± 0.00 a Mouthfeel 8.67 ± 8.66 c 7.0 ± 0.00 b 6.0 ± 0.00 a 6.0 ± 0.00 a Taste 8.0 ± 0.00 a 7.0 ± 0.00 a 8.0 ± 0.00 a 7.0 ± 0.00 a Overall acceptability 8.33 ± 0.28 d 7.0 ± 0.00 b 7.50 ± 0.00 c 6.0 ± 0.00 a a All the values are mean ± SD of three individual determinations b Means followed by the same superscript along the row are not significantly different using duncan multiple ranges test at 5% probability level (r = -0.93, P \ 0.01), dough stability (r = -0.94, P \ 0.01) and work of adhesion (r = -0.70, P \ 0.01).…”
Section: Physicochemical Properties Of Wheat Flours and Correlation To The Dough Rheological Properties Of Wheat Flourmentioning
confidence: 57%
“…Dough made of wheat (control) and wheat-amaranth blends were tested for spreadability using TA XT2 Stable Micro Systems Texture Analyser with a slight modification in the method by Arya, Ananthanarayan, Rodrigues, and Waghmare (2016). Dough of constant weight (8 g), diameter (25 mm), and thickness (13 mm) was placed below a 75 mm cylindrical probe.…”
Section: Dough Spreadabilitymentioning
confidence: 99%
“…Fractionation and reconstitution of wheat flour gluten protein and its subunit have made a significant effect on the functionality of gluten and its fraction in baking performance (Graßberger et al, 2003). Successful relationship of wheat fractions such as starch, gluten, and lipids on chapatti quality has been established through fractionation and reconstitution (Arya et al, 2016).…”
Section: Practical Applicationsmentioning
confidence: 99%